Politeness Strategies Employed by Lecturers in Undergraduate EFL Classroom - Septian Ardianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study investigates the politeness strategies employed by lecturers in EFL undergraduate online classroom. This study focuses on answering a research question; (1) how do the strategies employed by the lecturers in their teaching-learning activity. The qualitative method was used to fulfil the objective of the study. The data was collected from sit-in observation during their teaching-learning process. It was transcribed and analysed descriptively. The result shows that there are three strategies that employed by the lecturers namely positive politeness, negative politeness and bald-on-record. It can be concluded that this study will enrich the discussion which relates to the used of politeness strategies in teaching-learning program and how this study helps other lecturers/teacher to enrich their view in conducting kinds of strategies in their teaching-learning activity. Keywords: EFL Undergraduate Classroom, Online Classroom, Politeness Strategies